2023
DOI: 10.1007/s11883-023-01124-z
|View full text |Cite
|
Sign up to set email alerts
|

Statin Intolerance: an Overview of US and International Guidance

Abstract: Purpose of Review To review recent international and domestic definitions, considerations, and treatment algorithms for statin intolerance, and specifically, statin-associated muscle symptoms (SAMS). Recent Findings Multiple organizations around the world have produced guidance documents to aid clinicians on managing statin intolerance. A common theme resides among all the guidance documents that most patients can tolerate statins. For those patients who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Particular attention should be paid to issues related to the safety of intensive lipid-lowering treatment and prescription filing (frequency of drug intake). The world’s largest meta-analysis, conducted by Bytyci et al, including 4,143,517 patients, showed that statin intolerance occurred in only 9.1% of them (with only 1–3% for complete statin intolerance), while in an analysis limited to high-quality 112 randomized clinical trials, this percentage was lower and amounted to 4.9% [ 27 , 28 ]. The same lower ratios were observed when statin intolerance was diagnosed with approved definitions (5.9–7%)—what means than even 93% of patients might be treated with without any safety concerns, what makes statins one of the most tolerable drugs in cardiology.…”
Section: Problem With Adhering To Recommendations and Achieving Thera...mentioning
confidence: 99%
“…Particular attention should be paid to issues related to the safety of intensive lipid-lowering treatment and prescription filing (frequency of drug intake). The world’s largest meta-analysis, conducted by Bytyci et al, including 4,143,517 patients, showed that statin intolerance occurred in only 9.1% of them (with only 1–3% for complete statin intolerance), while in an analysis limited to high-quality 112 randomized clinical trials, this percentage was lower and amounted to 4.9% [ 27 , 28 ]. The same lower ratios were observed when statin intolerance was diagnosed with approved definitions (5.9–7%)—what means than even 93% of patients might be treated with without any safety concerns, what makes statins one of the most tolerable drugs in cardiology.…”
Section: Problem With Adhering To Recommendations and Achieving Thera...mentioning
confidence: 99%
“…While the lipid-lowering effects of the drugs above have been well-documented, there is a growing concern regarding their potential long-term side effects. Observational researches have indicated that these commonly prescribed medications may lead to muscle pain, soreness, and/or weakness [ 5 , 6 ]. Skeletal muscle-associated symptoms were reported by up to 20% of statin users [ 7 ].…”
Section: Introductionmentioning
confidence: 99%